MODERASI BERAGAMA DALAM PENDIDIKAN AGAMA ISLAM BERDASARKAN LITERATUR AL-QUR’AN DAN HADITS - Al Ayyubi, Ibnu Imam; Muhaemin, Abdul; Martini, Sofia; Andriani, Anita; Yasmin, Sabrina (SYAIKHONA: Jurnal Magister Pendidikan Agama Islam, 2024)
This research aims to outline religious moderation in Islamic education based on the Al-Qur'an and Hadith literature to equip students in the world of Islamic education to truly maintain their religious values and maintain unity and unity. This research is qualitative descriptive research with a literature study approach that refers to several research data sources and data collection techniques in the form of studies on religious moderation. The focus of the research that will be raised is the construction of religious moderation in Islamic education based on the literature of the Koran and Hadith. The data collection technique used in this research is the library research method, namely library study with the data analysis technique used in this research being the descriptive method. In this research, it can be concluded that moderation is paired with the words wasath or wasathiyah, or it could be paired with the word tawassuth. The root of this word is contained in the Al-Quran, namely in QS. Al-Baqarah verses 143 & 238, QS. Al-Qalam verse 28, and QS. Al-Adiyat verse 5. Thus, the implications for the Al-Quran and Hadith that can be coherence with Islamic religious education are that it is far from violence which has recently become increasingly common in the context of bullying, the existence of love of peace, a tolerant nature, maintains noble values well amid changing times. integrated with Westernization, a priority scale that prioritizes goodness, flexibility and always innovative for benefit-based reform.